The Influence of Leadership, Competence, and Compensation on Employee Performance at the Election Supervisory Body of Bantaeng Regency - Aslam, Imam; Jam’an, Andi; Anggoro, Yusuf Alfian Rendra (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The purpose of this study is to determine and examine how employee performance at the Bantaeng Regency Election Supervisory Board is impacted by leadership, skill, and pay. Using t-tests and multiple linear regression analysis, the study was carried out at the Bantaeng Regency Election Supervisory Board main office and sub-district supervisory offices (Panwaslu). Questionnaires are the main tool used in this quantitative study to collect data. 65 respondents who work for the Bantaeng Regency Election Supervisory Board participated in the study. The findings show that leadership has a favorable but not statistically significant impact on employee performance, as shown by the significance value P = 0.080 > 0.05 and the t-table value exceeding the t-count (1.669 > 1.7810). The t-table value is less than the t-count (1.668 < 4.906), with a significance value of P = 0.000 < 0.05, indicating a positive and substantial influence of the competence variable on performance. With a significance value of P = 0.002 < 0.05 and a t-table value less than the t-count (1.668< 3.243), compensation also has a positive and significant impact on performance. The model summary's R2 value, as determined by the R2 coefficient of determination test, is 0.843. This indicates that the independent variables of leadership, competence, and compensation can predict the dependent variable of employee performance by 84.3%, with other factors influencing the remaining 15.7%. Additionally, the output displays a R value of 0.665, suggesting a substantial correlation between employee performance and leadership, competence, and pay.